Harmonization of Civil Procedure (Washington University Global Studies Law Review, 2005)
The focus of the panel is the harmonization of differing civil procedure regimes in the transnational context. In the past few years, a great deal of work has been directed toward creating a rational transnational civil procedure system. This panel we consists of three of the true engines and luminaries in this field: Professor Hazard, Professor Taruffo, and Professor Gidi, all of whom have worked to fashion a body of innovative solutions to transnational civil procedure hurdles. Together, these three can provide a uniquely informed perspective on the challenges and structures of transnational civil procedure.
Keywords: Civil procedure; Harmonization of laws; International; United States